2012
DOI: 10.1073/pnas.1201362109
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Escherichia coli β-barrel assembly machine (Bam) is required for essential components to interact properly with substrate

Abstract: The outer membrane (OM) of Gram-negative bacteria such as Escherichia coli contains lipoproteins and integral β-barrel proteins (outer-membrane proteins, OMPs) assembled into an asymmetrical lipid bilayer. Insertion of β-barrel proteins into the OM is mediated by a protein complex that contains the OMP BamA and four associated lipoproteins (BamBCDE). The mechanism by which the Bam complex catalyzes the assembly of OMPs is not known. We report here the isolation and characterization of a temperature-sensitive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 22 publications
7
111
0
Order By: Relevance
“…However, BamD is an essential protein in bacteria and must therefore play an important role (23,37). We previously demonstrated that BamD interacts with unfolded OMPs (21,38), and here we have shown that interfering with that interaction inhibits β-barrel assembly in vitro and compromises cell growth and OM integrity in vivo. Together, these observations suggest that BamD's essential function is to bind unfolded OMP substrates during the assembly process.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, BamD is an essential protein in bacteria and must therefore play an important role (23,37). We previously demonstrated that BamD interacts with unfolded OMPs (21,38), and here we have shown that interfering with that interaction inhibits β-barrel assembly in vitro and compromises cell growth and OM integrity in vivo. Together, these observations suggest that BamD's essential function is to bind unfolded OMP substrates during the assembly process.…”
Section: Discussionmentioning
confidence: 91%
“…However, this conclusion does not imply that each of the >50 different OMPs present in the OM specifically requires BamD for its assembly (39). Other components of the Bam complex also interact with substrates (13,15,(19)(20)(21)(22)38) and may have functions that overlap with that of BamD such that certain OMPs can be assembled in its absence. Rather, we suggest that BamD's essentiality in substrate binding reflects a kinetic effect on In the in vitro experiments, full-length BamA substrates containing mutations in the β-signal sequence were denatured and then diluted into solutions containing 0.5% lauryldimethylamine-N-oxide (LDAO) or BamABCDE proteoliposomes to assess, respectively, the effects of the mutations on the stability of the folded β-barrel and on the folding mechanism carried out by the Bam complex.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the in vitro folding of OMPs significantly slows as the bilayer thickness approaches that of biological membranes (33), and folding occurs with low efficiency using membranes derived from E. coli (33), thus suggesting that E. coli membranes present a kinetic barrier to folding as a negative selection against incorporation into bacterial inner membranes. A key unknown in this scheme is the interaction energy with the outer membrane beta-barrel assembly machinery (BAM complex) that is known to be important for efficient OMP folding in cells and whose components are essential in E. coli (38,39). SurA is thought to participate in BAM-assisted folding of uOMPs (40), but the energy of this interaction is unknown as indicated by the question mark.…”
Section: Free Energy Of Folding May Be An Energy Sink For Sorting In Thementioning
confidence: 99%
“…Because there is no ATP in the periplasm [3], a uOMP appears to do all this directional sorting and folding in the absence of an external energy source once secreted through the translocon. Precise control of the OMP sorting and folding processes is paramount, because OMPs play many important roles in bacterial cells, and some of their functions are essential [4,5]. Equally important for control, however, is the possibility that OMPs could compromise the fitness of the cell if improperly inserted into the wrong membrane.…”
Section: Introduction: the Challenges Of Unfolded Outer Membrane Protmentioning
confidence: 99%